2019
DOI: 10.1108/hff-04-2019-0300
|View full text |Cite
|
Sign up to set email alerts
|

Impact of heat generation/absorption on the unsteady magnetohydrodynamic stagnation point flow and heat transfer of nanofluids

Abstract: Purpose The purpose of this study is to describe the unsteady three-dimensional magnetohydrodynamic stagnation point flow of nanofluids with heat generation/absorption. Design/methodology/approach The comprehensive numerical simulations in this study accommodate a physical insight into the heat transfer and flow problem. The use of finite difference method through the bvp4c function in Matlab provides the numerical results and graphical illustrations for the heat transfer rate and shear stress. Findings Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 27 publications
(28 reference statements)
0
16
0
Order By: Relevance
“…Bachok et al [6] concluded that inclusion of the unsteadiness parameter offers a significant impact towards the boundary layer flow in nanofluid and Fan et al [7] presented analytical solutions using the homotopy analysis method (HAM) and managed to advertise a highly precise analytical estimation which is in excellent agreement with the numerical results offered by the Keller box scheme. It is worth mentioning that a considerable amount of reviews on the unsteady stagnation point flow due to a stretching/shrinking surface have been accomplished by numerous researchers, including [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Bachok et al [6] concluded that inclusion of the unsteadiness parameter offers a significant impact towards the boundary layer flow in nanofluid and Fan et al [7] presented analytical solutions using the homotopy analysis method (HAM) and managed to advertise a highly precise analytical estimation which is in excellent agreement with the numerical results offered by the Keller box scheme. It is worth mentioning that a considerable amount of reviews on the unsteady stagnation point flow due to a stretching/shrinking surface have been accomplished by numerous researchers, including [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several researchers were also employing this solver for solving the boundary layer flow problems. 68–70…”
Section: Resultsmentioning
confidence: 99%
“…Energies 2019, 9, [43] investigated the non-Newtonian fluid and did stability analysis in order to indicate stable solutions. With existence of generation and absorption of heat, Jusoh et al [44] found multiple solutions and examined the stability of solutions. Triple solutions have been found for the micropolar nanofluid over shrinking surfaces by Lund et al [45].…”
Section: Problem Formulationmentioning
confidence: 99%